2021
DOI: 10.1016/j.bbagen.2021.129973
|View full text |Cite
|
Sign up to set email alerts
|

Cladosporols A and B, two natural peroxisome proliferator-activated receptor gamma (PPARγ) agonists, inhibit adipogenesis in 3T3-L1 preadipocytes and cause a conditioned-culture-medium-dependent arrest of HT-29 cell proliferation

Abstract: Background: Obesity and type 2 diabetes mellitus, which are widespread throughout the world, require therapeutic interventions targeted to solve clinical problems (insulin resistance, hyperglycaemia, dyslipidaemia and steatosis). Several natural compounds are now part of the therapeutic repertoire developed to better manage these pathological conditions. Cladosporols, secondary metabolites from the fungus Cladosporium tenuissimum, have been characterised for their ability to control cell proliferation in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…Typically, they are connected through the polymerization of the benzene ring of one α-naphthalone derivative with the benzene ring of another α-naphthalone derivative or the benzene ring of one α-naphthalone derivative with the cyclohexanone ring of another α-naphthalone derivative. The biological activities of α -naphthalenone dimer derivatives include anticancer, antimicrobial, and so on [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Two novel α -naphthalenone dimer derivatives were isolated and identified during the study of secondary metabolites of Neohelicosporium griseum .…”
Section: Discussionmentioning
confidence: 99%
“…Typically, they are connected through the polymerization of the benzene ring of one α-naphthalone derivative with the benzene ring of another α-naphthalone derivative or the benzene ring of one α-naphthalone derivative with the cyclohexanone ring of another α-naphthalone derivative. The biological activities of α -naphthalenone dimer derivatives include anticancer, antimicrobial, and so on [ 26 , 27 , 28 , 29 , 30 , 31 , 32 ]. Two novel α -naphthalenone dimer derivatives were isolated and identified during the study of secondary metabolites of Neohelicosporium griseum .…”
Section: Discussionmentioning
confidence: 99%
“…Another study emphasized the crucial role of FASN in CRC initiation, underlying its importance not only as a therapeutic target for early stages but also as a target for a preventive strategy [8]. Indeed, the use of FA synthase inhibitors for CRC treatment has obtained promising results, both in vitro and in vivo [42][43][44][45][46][47][48].…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, hexadecanedioic acid has been demonstrated to exhibit antimycotic activity [ 21 , 22 ] in few studies. Some metabolites from the fungus can inhibit cancer cell growth and migration [ 23 ] and induce cancer cell apoptotic death [ 24 ] in vitro. A previous study [ 25 ] also reported that hexadecanedioic acid was one of the identified biomarkers of the diagnostic panel for the early-stage CRC patients; however, it showed a decreasing trend compared to healthy individuals.…”
Section: Discussionmentioning
confidence: 99%